Pelatihan Media Dan Strategi Pembelajaran Matematika Realistik Berbasis Etnomatematika - Pramartha, I Nyoman Bagus; Dewi, Komang Hari Santhi; Putra, Wayan Andrika (Universitas Mataram, 2025)
This community service aims to improve teachers' knowledge and skills in teaching techniques at the senior high school level (SMA) in Susut Village through instructional media and realistic learning strategies based on ethnomathematics. With this training, it is hoped that teachers will be more innovative in conducting classroom learning, especially in mathematics learning. Instructional media can improve teachers' knowledge of technology that can support learning in the 4.0 era. Then, instructional media alone is not enough because in a media, of course, a strategy is needed in such a way in learning. Today's learning should be able to align technological sophistication without leaving behind customs and traditions that are close to the lives of students in Susut Village-Bangli. Therefore, the solution offered is the application of realistic learning based on ethnomathematics. The activities that have been carried out for 2 days are providing instructional media and realistic mathematics learning strategies based on ethnomathematics with 20 teachers. The results of measuring the achievement of the target of this activity show that the percentage of achievement of mastery of instructional media using the Flip.Pdf application before the training was 8.75% and there was an increase of 91.25% after the training took place. Likewise with the learning strategy training where only 32.5% of teachers understood how to develop learning strategies before the training was carried out. After the training, there was an increase of 67.5% of teachers who were able to develop learning strategies using a realistic mathematics approach based on ethnomathematics.